2015
DOI: 10.1111/jace.13756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Composition on the Molecular Structure of Synthesized Silicon Oxycarbides

Abstract: The dependence of silicon oxycarbides' chemical composition and molecular structure on their reaction conditions was tested by varying the atmosphere under which pyrolysis was performed. To obtain the silicon oxycarbides, densely cross‐linked silicone resin particles with an averaged diameter of 2 μm were pyrolyzed in various atmospheres of H2, Ar, and CO2, in the temperature range 700°C–1100°C. The residual mass of resin after pyrolysis was almost constant at 700°C, although their apparent colors varied disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…27 In this case, polysilsesquioxane is one example of an organosilicon polymer that can be transformed into aluminum silicate or silicon oxycarbide after heating at temperatures ≥700°C. 28,29 These results therefore account for the observed wetting of the alumina surface with aluminum.…”
Section: Methodssupporting
confidence: 59%
“…27 In this case, polysilsesquioxane is one example of an organosilicon polymer that can be transformed into aluminum silicate or silicon oxycarbide after heating at temperatures ≥700°C. 28,29 These results therefore account for the observed wetting of the alumina surface with aluminum.…”
Section: Methodssupporting
confidence: 59%
“…Recently, it was found that upon the proper choice of the pyrolysis atmosphere, two special SiOC compositions can be accessed: The pyrolysis of a polysilsesquioxane under hydrogen atmosphere leads to the selective elimination of the segregated carbon phase, whereas the pyrolysis of the same precursor under CO 2 atmosphere leads to the selective elimination of the network carbon . Thus, the thermal conversion of the precursor in H 2 atmosphere delivers an SiOC glass with negligible amount of segregated carbon; whereas its conversion in CO 2 delivers a nanocomposite consisting of vitreous silica and segregated carbon, that is, C/SiO 2 …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we assigned this band to "inorganic SiC", which appeared during pyrolysis as compensation of the sharp absorption band at 790 cm ¹1 assigned to organic SiCH 3 groups in precursors. 1), 3) In the 200 and 240°C samples, however, we observe a broadband absorption covering the range of 900850 cm ¹1 . They are possibly assigned to various kinds of SiC bonds which have different peak positions in terms of surrounding environments.…”
Section: )mentioning
confidence: 97%